EXPERIMENTAL STUDY ON THE INFLUENCE OF BLUNTING CRACK TIP ON MECHANICAL PROPERTIES OF CT SPECIMENS - ZHANG ZhuWu; XU ChengWei; LI Wei; GUO LiPing; PAN GuangGuo (Jixie qiangdu)
Mechanical properties of compact tensile（ CT） specimens were studied by plane fracture toughness test,fracture morphology characteristics of both tip crack and blunt crack specimens were analyzed,and the influence of crack tip blunting on mechanical properties was quantitatively analyzed. The experimental results show that the fracture toughness value,the maximum fracture value,the plastic component and the maximum displacement calculated by the tip crack are all smaller than the corresponding values of the blunting crack. The blunting zone formed at the crack tip is conducive to inhibiting crack propagation and improving the ability to resist fracture,which can achieve the purpose of crack arrest. With the increasing of the curvature radius of the crack tip,there is an optimal blunt crack curvature radius. When the radius of curvature exceeds its value,the stiffness slightly degrades,and the proportion of the plastic component in the input energy of the external load increases. The fracture toughness is significantly improved,which enhances the bearing capacity of the specimen. The results can provide scientific basis for quantitative evaluation of the influence of blunting crack tip on mechanical properties.